How do economic crises affect migrants' risk of infectious disease? A systematic-narrative review. - Kentikelenis, A; Karanikolos, M; Williams, G; Mladovsky, P; King, L; Pharris, A; Suk, J; Hatzakis, A; McKee, M; Noori, T; Stuckler, D (2015)
BACKGROUND: It is not well understood how economic crises affect infectious disease incidence and prevalence, particularly among vulnerable groups. Using a susceptible-infected-recovered framework, we systematically reviewed literature on the impact of the economic crises on infectious disease risks in migrants in Europe, focusing principally on HIV, TB, hepatitis and other STIs. METHODS: We conducted two searches in PubMed/Medline, Web of Science, Cochrane Library, Google Scholar, websites of key organizations and grey literature to identify how economic changes affect migrant populations and infectious disease. We perform a narrative synthesis in order to map critical pathways and identify hypotheses for subsequent research. RESULTS: The systematic review on links between economic crises and migrant health identified 653 studies through database searching; only seven met the inclusion criteria. Fourteen items were identified through further searches. The systematic review on links between economic crises and infectious disease identified 480 studies through database searching; 19 met the inclusion criteria. Eight items were identified through further searches. The reviews show that migrant populations in Europe appear disproportionately at risk of specific infectious diseases, and that economic crises and subsequent responses have tended to exacerbate such risks. Recessions lead to unemployment, impoverishment and other risk factors that can be linked to the transmissibility of disease among migrants. Austerity measures that lead to cuts in prevention and treatment programmes further exacerbate infectious disease risks among migrants. Non-governmental health service providers occasionally stepped in to cater to specific populations that include migrants. CONCLUSIONS: There is evidence that migrants are especially vulnerable to infectious disease during economic crises. Ring-fenced funding of prevention programs, including screening and treatment, is important for addressing this vulnerability.